Auditing - Ricchiute, David N. (South-Western/Thomson Learning, 2006)
The book takes an approach that is ideal for professionals: each chapter addresses 1) what are the audit implications of the accounting transaction in question, and 2) what are the legal liabilities, and ethical implications of the transaction. In addition, this text emphasizes the concepts and standards of independent auditing, and integrates contemporary audit methods with a focus on complex judgments and decision processes. Auditing methods, the newest technology for auditing, and professional responsibilities for auditors are all covered in depth